1998
DOI: 10.1080/15216549800203402
|View full text |Cite
|
Sign up to set email alerts
|

TNFα‐induced aerobic synthesis of ATP on plasma membranes of target cells. The relation to the expression of the nuclear oncogene c‐myc

Abstract: The accumulation of ATP by preparations of plasma membranes enriched particles (PMEP) isolated from rat hepatocytes, murine splenocytes and human T-lymphocytes has been investigated after the binding of human and murine tumour necrosis factors (TNFct) to their specific receptors. The TNFc~-induced expression of the nuclear oncogene c-myc in intact hepatocytes has been also studied. TNFc~ induced the marked biosynthesis of ATP on PMEP of hepatocytes and splenocytes within the first minute of incubation. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These experiments were carried out on PMEP isolated from human T lymphocytes. It was shown that the presence of only ADP (the substrate for adenylate cyclase) in the medium is insufficient for ATP biosynthesis on the plasma membrane, on the other hand, the presence of W,PS-di(adenosine-5')pentaphosphate in the incubation medium in concentrations suppressing adenylate cyclase did not inhibit ATP biosynthesis on the plasma membrane stimulated by tumor necrosis factors (TNF) [28].…”
Section: Plasma Membrane As Atp Generatormentioning
confidence: 98%
See 3 more Smart Citations
“…These experiments were carried out on PMEP isolated from human T lymphocytes. It was shown that the presence of only ADP (the substrate for adenylate cyclase) in the medium is insufficient for ATP biosynthesis on the plasma membrane, on the other hand, the presence of W,PS-di(adenosine-5')pentaphosphate in the incubation medium in concentrations suppressing adenylate cyclase did not inhibit ATP biosynthesis on the plasma membrane stimulated by tumor necrosis factors (TNF) [28].…”
Section: Plasma Membrane As Atp Generatormentioning
confidence: 98%
“…Studies of TNF<t showed that ATP synthesis induced in plasma membranes of mouse splenocytes and rat hepatocytes was completely inhibited with amiloride (Na+/H + exchange inhibitor and blocker of Na + influx) and the antitumor antibiotic adriamycin [28].…”
Section: Plasma Membrane As Atp Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…TNF alpha can cause liver cell apoptosis through the TNF-alpha receptor or Fas/CD95, which is expressed by liver cells. The TNF-alpha induced expression of the nuclear oncogene c-myc in intact hepatocytes has been studied [28] . The expression of Hsmycl is down-regulation, which may be the reason of preventing hepatic cell from apoptosis.…”
Section: Discussionmentioning
confidence: 99%